Removal of administrative barriers through the recent procedural simplifications in Slovenia and Croatia - Polonca Kovač; Vedran Ðulabic; Nevia Čičin-Šain (DANUBE: Law, Economics and Social Issues Review, 2017)
The removal of administrative barriers (RAB) is a constant policy at both European Union (EU) and national levels. Initially, RAB has been seen as a part of economically-driven Regulatory Impact Analysis, while lately a more interdisciplinary approach dominates, through Smart Regulation and Public Administration Reforms programs. Slovenia and Croatia, as "new" EU members, address the respective goals of streamlining mostly by amendments in sector-specific laws. Additionally, there is an open question regarding the implementation of these amendments. The aim of the article is to address the legally set procedural dimensions of red tape reduction in comparative and competitive settings. Hence, this article tackles the topic with analyses of the most recent procedural changes in recent years in selected Slovene and Croatian laws covering key administrative areas relevant for entrepreneurs, based on the World Bank's Doing Business rank, i.e. the registration of entrepreneurs, tax procedures and the issuing of construction permits. The results reveal that RAB in Slovenia and Croatia still highly lacks a systematic approach, and is mainly focused only normatively and in piecemeal manner. Consequently, we face an implementation gap. This study shows that the Slovene and Croatian examples can also serve as an illustration for other countries on how to improve their RAB policies, among others by introducing the modernisation of the Administrative Procedure Act as a leading administrative simplification measure.
Keywords: 330; Administrative Burden/Barriers; Procedural Law; Simplification; Entrepreneurship; Slovenia; Croatia; EU